'Video‐scats': combining camera trapping and non‐invasive genotyping to assess individual identity and hybrid status in gray wolf. Issue 1 (10th November 2017) - Canu, Antonio; Mattioli, Luca; Santini, Alberto; Apollonio, Marco; Scandura, Massimo
Abstract : Motion‐activated video cameras and non‐invasive genetic sampling are tools commonly used to obtain relevant information on wild populations of rare or elusive carnivores while minimizing disturbance. The two approaches are usually implemented separately, but they are occasionally integrated at a population level, mostly in order to estimate population size. Here we show the advantages of combining camera trapping and non‐invasive genotyping at an individual level, in a monitored Italian wolf population affected by introgression from domestic dogs. After 24 defecation events recorded by camera traps located at marking sites, samples ('video‐scats') were collected in order to determine the individuals' identity based on the analysis of sex markers, 11 autosomal microsatellites, two Y‐chromosome microsatellites and the control region of the mitochondrial DNA. Genetic data for 19 successfully genotyped scat samples were combined with morphological and behavioural traits observed in the videos and compared to data from ongoing genetic monitoring, all of which enabled us to determine sex, pack membership, breeding status, morphological traits (including those used to assess hybridization), sampling history, and introgression level of each individual. Finally we discuss the advantages and possible drawbacks of 'video‐scats', supporting their use as an opportunistic source of valuable data.